Wnt5A-Mediated Actin Organization Regulates Host Response to Bacterial Pathogens and Non-Pathogens - Jati, Suborno; Sengupta, Soham; Sen, Malini (Frontiers in Immunology, 2021)
Wnt5A signaling facilitates the killing of several bacterial pathogens, but not the non-pathogen E. coli DH5α. The basis of such pathogen vs. non-pathogen distinction is unclear. Accordingly, we analyzed the influence of Wnt5A signaling on pathogenic E. coli K1 in relation to non-pathogenic E. coli K12-MG1655 and E. coli DH5α eliminating interspecies variability from our study. Whereas cell internalized E. coli K1 disrupted cytoskeletal actin organization and multiplied during Wnt5A depletion, rWnt5A mediated activation revived cytoskeletal actin assembly facilitating K1 eradication. Cell internalized E. coli K12-MG1655 and E. coli DH5α, which did not perturb actin assembly appreciably, remained unaffected by rWnt5A treatment. Phagosomes prepared separately from Wnt5A conditioned medium treated K1 and K12-MG1655 infected macrophages revealed differences in the relative levels of actin and actin network promoting proteins, upholding that the Wnt5A-Actin axis operates differently for internalized pathogen and non-pathogen. Interestingly, exposure of rWnt5A treated K1 and K12-MG1655/DH5α infected macrophages to actin assembly inhibitors reversed the scenario, blocking killing of K1, yet promoting killing of both K12-MG1655 and DH5α. Taken together, our study illustrates that the state of activation of the Wnt5A/Actin axis in the context of the incumbent bacteria is crucial for directing host response to infection.